EXAMINING PERCEPTIONS OF SCIENCE AND TECHNOLOGY LITERACY OF CLASSROOM TEACHER CANDIDATES - Barış ÇAYCI; Nurhan ATALAY (International Journal of Eurasia Social Sciences, 2017)
One of the most important factors that will ensure that students acquire the knowledge, skills, attitudes and values needed to be educated as literate individuals depends on the teachers who will apply the program in their classes, as in all curricula. First of all, it is expected that teachers should have knowledge about science literacy for them to develop these skills in their students, knowledge about the activities that improve science literacy of students and their perception of competency is high. Self-efficacy perception is the individual’s perceived ability and capacity. It is expected that classroom teachers who will gain science and technology literacy in primary school have high self-efficacy perceptions related to themselves. In this context, it is important to determine the science and technology literacy perceptions of the classroom teacher candidates themselves. The purpose of this study is to determine the self-efficacy perceptions of science and technology literacy of the intended classroom teacher candidates. Mixed method was used in the research. The research was conducted with 219 class teacher candidates in the third and fourth grades of a university in Central Anatolia. The quantitative data were collected and analyzed by the screening model using the "Perception of Self- efficacy towards Science and Technology Literacy" developed by Caymaz (2008), then quantified by semi-structured interviews with 18 teacher candidates using criteria sampling. It was determined that the self-efficacy perception level of teacher candidates was "moderate enough" according to the average of the items on the scale in the research. It was also found that the self-efficacy perceptions of science and technology literacy of classroom teacher candidates showed a meaningful difference in terms of some variables.